2012
DOI: 10.1109/tbme.2012.2212896
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal Signal Analysis of Electroporation in Biological Cells

Abstract: Conductivity measurements in suspensions of biological cells have been used since many years for electroporation effectiveness evaluation. However, conductivity modeling by means of instantaneous values of current and voltage during pulse application does not take into account the effects of the sample reactance and the dielectric dispersion of the medium. This can lead to misinterpretation in the electroporation analysis. The electrical modeling and characterization of electroporation using sinusoidal signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(89 reference statements)
0
7
1
Order By: Relevance
“…In this way, differences in the results were independent from the cell density but due to the different conditions tested. In fact, considering a diameter of 25 to 30 mm for MG-63 cells, 55 the volume fraction of cells 56,57 in monolayer is 0.52 to 0.75 that gives an effective electric field that is 84% to 95% of the applied one. From these data it was determined that by applying 1000 V/ cm the transmembrane voltage is 3.15 to 8.56 V. This transmembrane voltage is larger with respect to the typical one to form cell membrane pores 58 (ie, 0.2-1 V).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, differences in the results were independent from the cell density but due to the different conditions tested. In fact, considering a diameter of 25 to 30 mm for MG-63 cells, 55 the volume fraction of cells 56,57 in monolayer is 0.52 to 0.75 that gives an effective electric field that is 84% to 95% of the applied one. From these data it was determined that by applying 1000 V/ cm the transmembrane voltage is 3.15 to 8.56 V. This transmembrane voltage is larger with respect to the typical one to form cell membrane pores 58 (ie, 0.2-1 V).…”
Section: Discussionmentioning
confidence: 99%
“…The numerical simulations that predict or confirm these experimental findings are an important tool for the treatment planning of electroporation. Numerous studies have shown that the cell suspension conductivity is increased due to membrane electropermeabilization . The local electric field distribution within the treated tissue also produces conductivity increase .…”
mentioning
confidence: 99%
“…New insight was obtained into the kinetics of diffusion due to the creation of new interfaces at low frequency, which leads to a current path increase, i.e., decreased conductivity even with the presence of membrane pores. M A N U S C R I P T 13 1,209×10 13 4,643×10 13 3,155×10 14 7,736×10 13 A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 28 Highlights -An experimental protocol was designed to elucidate pulsed electric field effects on the electrode/electrolyte interface. -An electric field affects electrodes and the degree of alteration depends on the electrolyte conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Electrode/electrolyte interface impedance has strong dispersion of resistance and reactance at low frequencies. Ion diffusion within a double layer of cells also results in low frequency dielectric dispersion [13,14]. On the other hand, when a high-voltage electric pulse is applied to an electrolyte solution, a variety of electrolysis reactions occur at the electrode-solution interfaces in addition to cell membrane permeabilization [15].…”
Section: Introductionmentioning
confidence: 99%